A step forward, but still inadequate: Australian health professionals' views on the genetics and life insurance moratorium. Issue 8 (20th September 2021) - Tiller, Jane M; Keogh, Louise A; McInerney-Leo, Aideen M; Belcher, Andrea; Barlow-Stewart, Kristine; Boughtwood, Tiffany; Gleeson, Penny; Dowling, Grace; Prince, Anya; Bombard, Yvonne; Joly, Yann; Delatycki, Martin; et al.
Abstract : Background: In 2019, the Australian life insurance industry introduced a partial moratorium (ban) limiting the use of genetic test results in life insurance underwriting. The moratorium is industry self-regulated and applies only to policies below certain financial limits (eg, 500 000 of death cover). Methods: We surveyed Australian health professionals (HPs) who discuss genetic testing with patients, to assess knowledge of the moratorium; reported patient experiences since its commencement; and HP views regarding regulation of genetic discrimination (GD) in Australia. Results: Between April and June 2020, 166 eligible HPs responded to the online survey. Of these, 86% were aware of the moratorium, but <50% had attended related training/information sessions. Only 16% answered all knowledge questions correctly, yet 69% believed they had sufficient knowledge to advise patients. Genetics HPs' awareness and knowledge were better than non-genetics HPs' (p<0.05). There was some reported decrease in patients delaying/declining testing after the moratorium's introduction, however, 42% of HPs disagreed that patients were more willing to have testing post-moratorium. Although many (76%) felt the moratorium resolved some GD concerns, most (88%) still have concerns, primarily around self-regulation, financial limits and the moratorium's temporary nature. Almost half (49%) of HPs reported being dissatisfied with the moratorium as a solution to GD. The majority (95%) felt government oversight is required, and 93% felt specific Australian legislation regarding GD is required. Conclusion: While the current Australian moratorium is considered a step forward, most HPs believe it falls short of an adequate long-term regulatory solution to GD in life insurance.